(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Bibliotherapy is presented as one of six therapeutic modes of being-in-the-world that were concentrated in the Asclepieia, the holistic healing centres of Ancient Greece. An experiential exercise in therapeutic reading, alongside findings with present-day participants, is used to explore possible reasons for the centrality of bibliotherapy in the Ancient therapeutic practice and its continuing importance today in people’s self-therapeutic experiences.